(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study investigates the relationship and impact of transformational leadership, communication, and digital transformation on teacher performance. The research involved 56 teachers from MTs Ittihadul Mukhlisin as respondents. Data were tested for reliability using Cronbach’s Alpha, with results exceeding 0.700, indicating that all variables were reliable. Multiple linear regression analysis was then applied to assess the effects of the independent variables. The findings reveal that transformational leadership and communication significantly and positively influence teacher performance, whereas digital transformation does not show a significant effect. These results were further confirmed by the t-test conducted on each independent variable.